2018
DOI: 10.1186/s12859-018-2339-3
|View full text |Cite
|
Sign up to set email alerts
|

Linked open data-based framework for automatic biomedical ontology generation

Abstract: BackgroundFulfilling the vision of Semantic Web requires an accurate data model for organizing knowledge and sharing common understanding of the domain. Fitting this description, ontologies are the cornerstones of Semantic Web and can be used to solve many problems of clinical information and biomedical engineering, such as word sense disambiguation, semantic similarity, question answering, ontology alignment, etc. Manual construction of ontology is labor intensive and requires domain experts and ontology engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…To summarize, we conclude that most of the approaches used for automatic ontology generation from unstructured text corpus are domain-specific, demonstrating the need for domain independent ontology-generation methods [3,4]. Additionally, few systems used unstructured text from external heterogeneous sources [17,18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To summarize, we conclude that most of the approaches used for automatic ontology generation from unstructured text corpus are domain-specific, demonstrating the need for domain independent ontology-generation methods [3,4]. Additionally, few systems used unstructured text from external heterogeneous sources [17,18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many previous studies have revealed the effectiveness of semantic search engines over conventional keyword search engines when dealing with NLQ in several domains, among which are the biomedical field [46], expert systems [47], transportation [48], and forensics [49]. Meanwhile, reference [46] offered an automatic generation framework for novel ontology, called the linked open data (LOD) method for automatic biomedical ontology generation (LOD-ABOG), which is powered by LOD. The LOD-ABOG was utilized with the aim of extracting concepts utilizing KBs, mainly the medical system of language UMLS and LOD, together with the operation of NLP.…”
Section: Ontologymentioning
confidence: 99%
“…Recently, several approaches that reuse existing knowledge bases to automate ontology construction from unstructured text have been proposed [24][25][26]. The drawbacks of these approaches include labour costs to construct the dictionary, its domain-specific nature and the limited number of patterns.…”
Section: Related Workmentioning
confidence: 99%